Qual o resultado de: 2y. (-2y)?
Soluções para a tarefa
Respondido por
3
-4y². -2.2 = -4 y.y = y²
2y. (-2y) = -4y².
2y. (-2y) = -4y².
Respondido por
1
Vamos lá :
2y . (- 2y)
2(-2) . y.y ==> Realiza o jogo de sinal { + com - = - } .
= - 4 y²
Espero ter ajudado !!!
2y . (- 2y)
2(-2) . y.y ==> Realiza o jogo de sinal { + com - = - } .
= - 4 y²
Espero ter ajudado !!!
Perguntas interessantes
Matemática,
1 ano atrás
Português,
1 ano atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Português,
1 ano atrás
Pedagogia,
1 ano atrás
Matemática,
1 ano atrás